Innovative Development of Mobile Application for Qibla Direction Guidance Services Training - Fajar Fathurahman (Ilomata International Journal of Social Science, 2020)
This study aims to produce software in the Qibla Direction Determination that is created using a web-based application and can be accessed optimally via an android based-cellular phone. This research uses the Research and Development method by adapting the ADDIE development model which consists of five (5) stages, namely Analysis, Design, Development, Implementation, and Evaluation. This Research was conducted on technical staff at the office in the Ministry of Religion of Kepulauan Seribu Region. The result of this research trial found that the media that had been developed were suitable for use and made the training process and also its applications easier and more affordable. The results of this study indicate that the use of mobile applications in the Qibla Direction Guide Service Training that is applied with the blended learning model can improve participants' understanding of the concept of calculation Qibla Direction Determination that can be applied interactively, collaboratively and also integratively between science and technology.